Transfer of Technology to Utilize Tumbu Sugar by-Products as a Medium for White Oyster Mushroom Plants to Improve the Creative Economy of Kandangmas Village - Zulfikar Rafi Nurcahyandi; Erly Nurviyani; Andre Widiatmoko; Pria Jaya Permadi; Jayanti Putri Purwaningrum (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This community service is motivated by a large amount of waste from the by-products of tumbu sugar in Kandangmas Village reaching 6 tons per day. The bagasse waste is only burned and landfilled without being used, this causes environmental pollution in Kandangmas Village and until now there has been no solution to reduce the waste. The purpose of this community service is to utilize the by-products of tumbu sugar in making white oyster mushroom backlogs. and knowing the economic improvement of partners during the mushroom cultivation and processing of white oyster mushroom products. The method applied is Participatory Action Research (PAR). Data collection used includes interviews and document analysis. Based on observations, it is known that the percentage of fungal growth in beetles reaches 95%. The resulting mushroom has good quality, it is characterized by white mushrooms, heavy bots, and a wide diameter. Post-harvest oyster mushroom handling is processing and marketing. Currently, residents already have around 20 processed mushroom menus which are sold at the Aosy Lady Mushroom Lapak and market online as well. This shows that the training and mentoring from this community service activity have succeeded in increasing the knowledge and understanding as well as the community's economy related to the technical cultivation of white oyster mushrooms. In further activities, the ORMAWA HIMATIKA UMK PPK Team plans to conduct more intensive assistance and motivate the Environmental Care Plantation Community Group to become a mushroom center village and the only mushroom education village in Kudus Regency.